DFT Study of Cu₂O/Carbon-Based Nanomaterials Interacting with Zn and ZnS - Ibrahim Abbas, Ahmed; Shwya, Abbas; B., Soukaina; Setti, Larbi (University of Thi-Qar Journal of Science, 2025)
Copper oxide (I)/carbon-based nanomaterials have a great attention nowadays due to their potential in electronic and thermoelectric applications. In this study, density functional theory (DFT) was applied using the B3LYP hybrid function and the B3LYP 6-31G basis set to study the properties of (6Cu2O/C17) and (4Cu2O/C8) structures, as well as their interactions with zinc sulphide (ZnS) and zinc (Zn). The calculations included the determination of molecular geometry, contour density maps, electrostatic potential surfaces, spectra, HOMO and LUMO energies, band gap, dipole moment, polarizability, point group symmetry, and three states (DOS). The results showed that the interaction between (6Cu2O/C17) and (Zn, ZnS) led to a clear charge transfer and exchange, which was reflected in the density and electrostatic potential maps. The structures (6Cu2O/C17), (6Cu2O/C17–Zn), and (6Cu2O/C17–ZnS) also revealed narrow band gaps (~0.3 eV), which enhances their thermoelectric properties. Furthermore, interaction with ZnS increased the dipole moment from (2.99 Debye) to (15.33 Debye), indicating its potential for use in high dielectric materials. The (4Cu2O/C8) structure showed Cs group symmetry, which makes it important for optical applications. DOS maps also showed the emergence of new energy states resulting from interaction with Zn and ZnS. These results demonstrate that the studied nanostructures possess promising electronic, optical, and thermoelectric properties, qualifying them for practical applications in energy conversion and advanced device fabrication.